Derek Bok Center Series on College Teaching. 4, The Art Of The Lecture: Justice, A Harvard University Course In Moral Reasoning - Simon, Jamil; Harvard University. Derek Bok Center for Teaching and Learning (Cambridge, MA : Derek Bok Center for Teaching and Learning, 2007)
This video by the Derek Bok Center for Teaching and Learning is about using lectures as a part of teaching college courses.
Title from resource description page (viewed September 19, 2016).
In English.
Keywords: Teaching; Lecture method in teaching; College teachers; Enseignement magistral; College teachers; Lecture method in teaching; Teaching; Streaming videos; Instructional films; Instructional films; Films de formation